Evaluation of serum vascular cell adhesion marker-1 in β- thalassemia major patients - Al-Sarai, Nuha Abd Ali; Al-Mudallal, Subh Salim; Najm, Rana Rai'd (Iraqi Journal of Hematology, 2025)
BACKGROUND: Defects in the production of one or more hemoglobin chains result in a set of hereditary hematologic illnesses known as thalassemias. Alpha and β-thalassemia are the two primary thalassemia classifications. The pathophysiology of β-thalassemia is significantly influenced by endothelial activation markers, such as vascular cell adhesion molecule 1 (VCAM-1), which have been found to be higher in both transfusion-dependent and nontransfusion-dependent thalassemia patients. These markers have been suggested for the follow-up of vascular disease in this patient group. OBJECTIVES: The aim of this study was to evaluate the level of soluble VCAM-1 in β-thalassemia major patients and to correlate its level with the clinical parameters. PATIENTS, MATERIALS AND METHODS: This case-control study was enrolled on 40 patients with β-thalassemia major. They were collected from Thalassemia Center of Babylon Maternity and Pediatrics Teaching Hospital, from December 28, 2022, to March 30, 2023. Twenty of them were splenectomized, others were not. Another 40 apparently healthy individuals with no family history of thalassemia or other hemoglobinopathy were enrolled in this study as controls. The samples were collected to assay the human VCAM-1 using enzyme-linked immunosorbent assay based on the biotin double antibody sandwich technology. RESULTS: Among 80 subjects, age and body mass index were similar across groups. There are differences in complete blood count (CBC) parameters between thalassemic and control groups. Thalassemic patients displayed notably higher levels of VCAM-1 and ferritin compared to controls and in splenectomized patients than nonsplenectomized patients. There is a high significant correlation exists between VCAM-1 and ferritin, VCAM-1 and various CBC parameters. CONCLUSIONS: There are higher levels of VCAM-1 in β-thalassemia major patients compared to the control and in splenectomized compared to non-splenectomized patients which usually associated with disease complications, furthermore it reflect endothelial activation and dysfunction.